2003
DOI: 10.1038/sj.bjp.0705447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GABA agonists on body temperature regulation in GABAB(1)−/− mice

Abstract: Activation of GABAB receptors evokes hypothermia in wildtype (GABAB(1)+/+) but not in GABAB receptor knockout (GABAB(1)−/−) mice. The aim of the present study was to determine the hypothermic and behavioural effects of the putative GABAB receptor agonist γ‐hydroxybutyrate (GHB), and of the GABAA receptor agonist muscimol. In addition, basal body temperature was determined in GABAB(1)+/+, GABAB(1)+/− and GABAB(1)−/− mice. GABAB(1)−/− mice were generated by homologous recombination in embryonic stem cells. Corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 21 publications
6
61
1
1
Order By: Relevance
“…There are reports of other flavonoidtype molecules like quercetin [55] or flavonoid-enriched extracts [56] interfering with haloperidol-induced catalepsy with different outcomes but the present results suggest that luteolin has a baclofen-like effect in this test. However, it must be noted that unlike baclofen [57], luteolin did not produce any significant reduction in the animals' body temperature (results not shown).…”
Section: Discussionmentioning
confidence: 84%
“…There are reports of other flavonoidtype molecules like quercetin [55] or flavonoid-enriched extracts [56] interfering with haloperidol-induced catalepsy with different outcomes but the present results suggest that luteolin has a baclofen-like effect in this test. However, it must be noted that unlike baclofen [57], luteolin did not produce any significant reduction in the animals' body temperature (results not shown).…”
Section: Discussionmentioning
confidence: 84%
“…In a variety of paradigms, it has been shown that BALB/c mice exhibit increased anxiety-related behaviors compared to other inbred strains of mice (Belzung and Griebel, 2001). The use of mice on this background strain was essential for the generation of GABA B -related knockout animals, as mice on other background strains died very prematurely (Prosser et al, 2001;Queva et al, 2003). Interestingly, unlike genetic deletion, chronic pharmacological antagonism of GABA B receptors with CGP56433A failed to alter anxiety-related behavior in the light-dark box ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, mice that lack the GABA B(1) subunit (Prosser et al, 2001;Queva et al, 2003;Schuler et al, 2001) have been generated. Secondly, with positive allosteric modulators, novel pharmacological tools for GABA B receptors have been characterized (Urwyler et al, 2001;Urwyler et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study using hypothalamic medial preoptic slices revealed that both GABAA and GABAB receptor agonists inhibit neuronal tonic activity, implying a potential of GABA receptor agonists to modulate the Ztn [78]. In murine GABAB knockout and partial knockdown models, hypothermic responses were observed in GABAB +/-and wild type (GABAB +/+ ) mice but remained absent in GABAB -/-mice, supporting the notion that GABA receptors regulate temperature homeostasis via the Ztn [77]. Despite the established pentobarbital-GABA signaling link and the apparent relationship between GABA receptor agonism and Tb control, the evidence is presently too scant to classify pentobarbital as an anapyrexic agent.…”
Section: Pentobarbitalmentioning
confidence: 73%
“…Despite the widespread view that pentobarbital has no anapyrexic effects, more recent studies suggest that γ-aminobutyric acid (GABA) receptors, the main target of pentobarbital, may play a role in thermal homeostasis [77]. An in vitro study using hypothalamic medial preoptic slices revealed that both GABAA and GABAB receptor agonists inhibit neuronal tonic activity, implying a potential of GABA receptor agonists to modulate the Ztn [78].…”
Section: Pentobarbitalmentioning
confidence: 99%